Late Adolescents' Texting Experiences with Family: Mixed-Method Analysis for Understanding Themes and Sentiments - Xiaoran Sun; Jodi Dworkin; Samantha LeBouef (MDPI AG, 2023)
(1) Background: Texting is a prevalent communication method between late adolescents and their families that has implications for their relationships and well-being. This study used mixed-method analysis to understand what late adolescents, specifically college students, text their families about (i.e., themes), and how they feel about their family texting experiences (i.e., sentiments). (2) Methods: Our analyses used text transcripts of semi-structured individual interviews from 19 college students (aged 18-22 years, 13 female, 10 students of color), with 357 sentences/passages coded in total. (3) Results: Inductive content analysis revealed four themes: emotional support, relationship maintenance, conflict, and difficult conversations. Quantitative sentiment analysis revealed the highest level of positive sentiment attached to emotional support, and the highest level of negative sentiment attached to difficult conversations. The interviews that covered more conflict-based themes tended to have higher positive and negative sentiments. Differences between participants texting with their mothers and fathers were also revealed. (4) Conclusions: This research advances the understanding, in terms of both content and emotions, of the texting interactions with family members among late adolescents, along with providing methodological contributions, by highlighting the utility of the mixed-method analysis of interview data.